The SILCC (SImulating the LifeCycle of molecular Clouds) project -: II. Dynamical evolution of the supernova-driven ISM and the launching of outflows - Girichidis, Philipp; Walch, Stefanie; Naab, Thorsten; Gatto, Andrea; Wünsch, Richard; Glover, Simon; Klessen, Ralf S.; Clark, Paul C.; Peters, Thomas; Derigs, Dominik; Baczynski, Christian (Monthly notices of the Royal Astronomical Society, 2016)
The SILCC project (SImulating the Life-Cycle of molecular Clouds) aims at a more self-consistent understanding of the interstellar medium (ISM) on small scales and its link to galaxy evolution. We present three-dimensional (magneto)hydrodynamic simulations of the ISM in a vertically stratified box including self-gravity, an external potential due to the stellar component of the galactic disc, and stellar feedback in the form of an interstellar radiation field and supernovae (SNe). The cooling of the gas is based on a chemical network that follows the abundances of H+, H, H2, C+, and CO and takes shielding into account consistently. We vary the SN feedback by comparing different SN rates, clustering and different positioning, in particular SNe in density peaks and at random positions, which has a major impact on the dynamics. Only for random SN positions the energy is injected in sufficiently low-density environments to reduce energy losses and enhance the effective kinetic coupling of the SNe with the gas. This leads to more realistic velocity dispersions (σ_HI ~ 0.8σ_(300-8000K) ~ 10-20km/s, σ_Hα ~ 0.6σ_(8000-3e5K) ~ 20-30km/s), and strong outflows with mass loading factors of up to 10 even for solar neighbourhood conditions. Clustered SNe abet the onset of outflows compared to individual SNe but do not influence the net outflow rate. The outflows do not contain any molecular gas and are mainly composed of atomic hydrogen. The bulk of the outflowing mass is dense (ρ ~ 1e-25-1e-24g/cc) and slow (v ~ 20-40km/s) but there is a high-velocity tail of up to v ~ 500km/s with ρ ~ 1e-28-1e-27g/cc.